Photocurrent spectra of semi-insulating GaAs M–S–M diodes: Role of the contacts. (April 2016) - Dubecký, František; Oswald, Jiří; Kindl, Dobroslav; Hubík, Pavel; Dubecký, Matúš; Gombia, Enos; Šagátová, Andrea; Boháček, Pavol; Sekáčová, Mária; Nečas, Vladimír
Abstract: Current–voltage ( I–V ) characteristics and photocurrent (PC) spectra (600–1000 nm) of the metal–semiconductor–metal (M–S–M) structures based on high-quality undoped semi-insulating (SI) GaAs with AuGeNi backside contact and different semitransparent top contacts (AuGeNi, Pt, Gd and Nd) are reported, and analysed with the help of a simple physical model. It is shown that the dominant peak in the PC spectra and the change of photocurrent sign can be explained by a presence of two Schottky-like barriers at the top and bottom surfaces. In addition, I–V and PC results show dependence on the bias and its polarity, and on the contact metal used. The possible origins of these effects are discussed.